PERAN PEMERINTAH DAERAH DALAM PENGELOLAAN PASAR TRADISIONAL KECAMATAN DUA PITUE KABUPATEN SIDENRENG RAPPANG - Rahayu, Sri Suci; Mustanir , Ahmad; Yasin, Akhmad (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
Traditional markets play a crucial role in meeting the basic needs of the community, especially in rural areas. This study aims to explore the role of local government in managing the Tanru Tedong Traditional Market in Dua Pitue District, Sidenreng Rappang Regency. This research employs a qualitative approach with in-depth interviews and field observations involving local government officials and market traders. Data were analyzed using Nvivo 12 Plus software to identify key patterns and themes. The findings reveal that the local government acts as both a regulator and motivator in market management. As a regulator, the government sets policies to ensure the market operates orderly and efficiently, though challenges remain in changing the habits of traders and visitors. As a motivator, the government strives to encourage traders to increase productivity and maintain market cleanliness, despite ongoing challenges in waste management. Transparent market management and open communication between management and traders are deemed essential for improving market management effectiveness. Additionally, the market's security is considered adequate, though improvements in waste management and orderliness are still needed. The study concludes that synergy between local government and traders is vital for achieving effective and efficient market management, ultimately enhancing community welfare and business sustainability in traditional markets.